Identifying and Analyzing Risks of Under Bid Price Contracts on Government Construction Projects in West Sumatra - Amy Rahmadian Puteri; Akhmad Suraji; Benny Hidayat (Universitas Negeri Padang, 2025)
This study analyzes the risks associated with under bid price contracts on construction projects in West Sumatra, a phenomenon that shows a significant increase from 7.28% in 2015 to 32% in 2020. This study is focused on the local context of West Sumatra, providing new insights into competitive dynamics and business practices that may be unique to this region, in contrast to previous studies that may be general or regional in nature. The research objective is to identify and analyze the risk factors that arise from this under bidding practice. Through a specially designed questionnaire survey distributed to 30 local contractors in West Sumatra, and data processing using the SIRISPRO application, this study quantified and identified three main risks: specification deviations and design changes, contract criticism, and price increases during execution. The results showed that contractors responded to these risks by conducting evaluation and inspection of specifications, correction of deviations, and evaluation of personnel and acceleration of work. The implication of these findings is the need to evaluate government project contract management policies, particularly related to bidding regulations and more comprehensive bid evaluation, to mitigate the risk of under bidding and ensure the sustainability of quality construction projects in West Sumatra.